THE LINGUISTIC CHALLENGES OF MATHEMATICS WORD PROBLEMS: A RESEARCH AND LITERATURE REVIEW (Malaysian Journal of Learning and Instruction, 2017)
Purpose â€“ Word problems are still considered challenging for students when compared to other type of mathematics problems. Many emerging findings regarding this issue highlight that the challenges are predominately caused by linguistic aspects. This article aims to present a review and synthesis of literatures regarding the linguistic challenges of mathematics word problems and recommend solutions to address these challenges.Methodology â€“ Systematic search was done and 35 articles from inside and outside Indonesia were selected. The linguistic challenges and recommended solutions found were analyzed using the main features constructing mathematics language: multiple semiotic system, particular features of vocabulary and grammar, and complex syntax.Findings â€“ The review shows various difficulties shown by students in each feature of mathematics language. The review also recommends the practice of mathematics teaching and learning in which language aspects are discussed and exercised both among students and between the students and the teacher in order to help students face their linguistics challenges. It is also imperative for teachers to understand the structure and linguistic features involved in constructing word problems.Significance â€“ This review breaks down the difficulties of mathematics word problems from the perspective of linguistic features constructing them. The findings of this review offer teachers  different point of view to deal with teaching word problems, which is by understanding word problem as an entity of language rather than only as an entity of mathematics. This review also provides some solutions to help teachers address the difficulty for each linguistic feature.